Epidemiology Summer Course 2023 “Vaccine-Preventable Diseases: from Paediatric to Adult Targets” 22-24 November 2023 / Muhammad Radhi Rahimi Abu Bakar and Wan Ismahanisa Ismail - Abu Bakar, Muhammad Radhi Rahimi; Ismail, Wan Ismahanisa (UiTM Global @ Office of International Affairs, 2024)
On November 22, 2023, the International Epidemiology Summer Course 2023, "Vaccine-Preventable Diseases: From Paediatric to Adult Targets," took place at Fakultas Kesehatan Masyarakat, Universitas Airlangga (UNAIR), Surabaya, Indonesia, in partnership with the Faculty of Health Science, Universiti Teknologi MARA (UiTM), Pulau Pinang Branch, Malaysia. Fakultas Kesehatan Masyarakat, Universitas Airlangga, supports this course with an amount of Rp 30.000.000 (Thirty Million Rupiah), equivalent to RM9000. We invited about 12 staff and students to this summer course, which ran for 3 days from the 22 to the 24 November 2023. Other than student outbound programs, the primary objective is to achieve involvement in community and international conferences. This course facilitated an open and constructive dialogue between academia and diverse sectors of public health. The objectives of this course are to learn about vaccinepreventable diseases with epidemiological approaches and to share Vaccine Preventable Disease (VPD) preventive measures in Indonesia and other countries.